SENTRA JAJANAN SEHAT DI KAMPUNG SAYUR LANDASAN ULIN UTARA BANJARBARU - Chairil Zidane; Anna Octaviana (ULM Press, 2021)
Kampung Sayur in North Landasan Ulin (LAURA) sub-district, Banjarbaru City, is an agro-industrial area where various types of vegetable crops and healthy snacks that are produced and marketed by local SMEs can be found there. However, there are no proper infrastructures to develop all existing potencies in Kampung Sayur and commercial facilities to promote and sell healthy snacks at this time, so the healthy hawker center design by using Architectural Programming method is needed to solve those problems. Culinary Topography concept is applied in landscape, interior, and forms of the building that can optimize the commercial functions of the area.